2010
DOI: 10.1007/s00382-010-0770-x
|View full text |Cite
|
Sign up to set email alerts
|

The variable link between PNA and NAO in observations and in multi-century CGCM simulations

Abstract: The link between the Pacific/North American pattern (PNA) and the North Atlantic Oscillation (NAO) is investigated in reanalysis data (NCEP, ERA40) and multicentury CGCM runs for present day climate using three versions of the ECHAM model. PNA and NAO patterns and indices are determined via rotated principal component analysis on monthly mean 500 hPa geopotential height fields using the varimax criteria. On average, the multicentury CGCM simulations show a significant anti-correlation between PNA and NAO. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 77 publications
7
46
1
Order By: Relevance
“…Raible et al (2001) identified periods during which decadal-scale variability of the NAO coincides with strong coupling of the atmosphere to the ocean underneath, whereas periods dominated by interannual variability seem to be related to tropical SST changes in the Pacific. In line with these changes, the coupling between the Atlantic and Pacific is found to be variable over time (Raible et al, 2004;Pinto et al, 2011). Other reasons such as stratosphere-troposphere interaction (Kodera et al, 1996;Woollings et al, 2010a) or sea-ice interaction with the atmosphere (e.g.…”
Section: Climmentioning
confidence: 78%
“…Raible et al (2001) identified periods during which decadal-scale variability of the NAO coincides with strong coupling of the atmosphere to the ocean underneath, whereas periods dominated by interannual variability seem to be related to tropical SST changes in the Pacific. In line with these changes, the coupling between the Atlantic and Pacific is found to be variable over time (Raible et al, 2004;Pinto et al, 2011). Other reasons such as stratosphere-troposphere interaction (Kodera et al, 1996;Woollings et al, 2010a) or sea-ice interaction with the atmosphere (e.g.…”
Section: Climmentioning
confidence: 78%
“…Second, there is a clear Rossby wave train pattern arching from the Pacific into the Atlantic. Several studies have shown that the propagation of wave activity from the Pacific to the Atlantic can be an important factor in the onset of jet stream regimes in the North Atlantic (Franzke et al 2004;Strong and Magnusdottir 2008a,b;Cassou 2008;Lin et al 2009;Pinto et al 2011). Figure 7 shows the subsequent evolution of the streamfunction.…”
Section: Dynamical Analysismentioning
confidence: 99%
“…One possibility is that the remnants of the low-frequency Pacific wave train act to enhance the Atlantic transient eddy activity, perhaps by encouraging advection of air along the strong baroclinic zone over the east coast of North America (cf. Pinto et al 2011).…”
Section: Dynamical Analysismentioning
confidence: 99%
“…Occasionally, the GS activity can affect Europe (Stohl et al 2008;Lavers et al 2011). The GS maximum has also been hypothesized to play a role in linking large-scale climate fluctuations between the North Pacific/North America and the North Atlantic (Pinto et al 2011).…”
Section: Introductionmentioning
confidence: 99%